Man-Made Disaster : Lessons Learnt from Recent February 6, 2023 Turkey Earthquake of Magnitude Mw 7.8 - Srivastava, Amit (AMC Indian Journal of Civil Engineering, 2024)
"The Best Creator on the Earth after God is Civil Engineer" (quoted by unknown) as they work exuberantly for the built environment and create a livable world for us. This requires extreme engineering from planning, analysis, design, construction, and maintenance to demolition. If anything goes wrong at any stage, it can prove to be a disaster and because there is no retake in the profession, it may lead to huge economic loss to the society or nation including loss to thousands of lives. Such disasters are sometimes so huge that it can be categorized as man-made disaster and the world has witnessed the same in the recent Turkey earthquake of magnitude Mw = 7.8 in which total damage is estimated to be US $118.8 billion, leading to total casualties 59,259 deaths, 1,21,704 injured, and 297 missing. Major casualties were due to widespread damage or collapse of buildings and infrastructure that were expected to protect the people but they actually proved devil for them. Forensic investigation revealed some shocking evidence of poor design and construction practices that prevailed. For example, slab directly resting on columns, thick slab on thin columns, insufficient longitudinal bars or stirrups etc. The manuscript presents the outcome of some of those studies that will help future engineers who wish to venture in the Civil Engineering profession and willing to learn from failure of case studies.